2005
DOI: 10.1111/j.1743-6109.2005.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Erectile Dysfunction and Sleep Disorders Measured by Self-Assessment Questionnaires in Adult Men

Abstract: Background Erectile dysfunction (ED) is often associated with sleep disorders and sleep apnea syndrome (SAS) in mostly middle-aged and elderly men. Sleep disorders and ED are also prevalent in younger men. Purpose To study the association between ED, sleep disorders, and SAS, particularly among adult men. Methods A health screening program is offered by the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
(55 reference statements)
2
21
1
4
Order By: Relevance
“…Supporting these findings, studies of nocturnal penile tumescence in men with ED revealed a high rate of sleep disorders ranging from 44% to 61% [6][7][8]. Recently, Heruti et al [9] reported on the close relation between OSA and ED, so that either of them should be considered whenever the other is suspected in adult men.…”
Section: Introductionmentioning
confidence: 85%
“…Supporting these findings, studies of nocturnal penile tumescence in men with ED revealed a high rate of sleep disorders ranging from 44% to 61% [6][7][8]. Recently, Heruti et al [9] reported on the close relation between OSA and ED, so that either of them should be considered whenever the other is suspected in adult men.…”
Section: Introductionmentioning
confidence: 85%
“…ED, the inability to achieve or maintain an erection sufficient for sexual intercourse, 17 can arise due to hormonal, 18 vascular, 19 neurological, psychological and endocrinological disorders. 13 It is evident that obese men have a higher incidence of ED affecting their sexual life.…”
Section: Discussionmentioning
confidence: 99%
“…and further detailed by Schmidt and Wise in 1981 19. Since then, higher prevalences of ED in the OSA groups have been published in numerous studies,202122232425 depending on the diagnostic tool used. The prevalence of ED is as high as 69%,262728 with poorer sexual function in OSA patients compared with control patients matched for comorbidities and age 2325293031.…”
Section: Resultsmentioning
confidence: 98%
“…Since then, higher prevalences of ED in the OSA groups have been published in numerous studies,202122232425 depending on the diagnostic tool used. The prevalence of ED is as high as 69%,262728 with poorer sexual function in OSA patients compared with control patients matched for comorbidities and age 2325293031. This growing evidence leads to the recommendation in some papers of asking the patients about sleep disturbances,25323334 or even snoring35 during ED assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation